Early response to chemoradiotherapy for nasopharyngeal carcinoma treatment: Value of dynamic contrast‐enhanced 3.0 T MRI. Issue 6 (18th August 2014) - Zheng, Dechun; Chen, Yunbin; Liu, Xiangyi; Chen, Ying; Xu, Luying; Ren, Wang; Chen, Weibo; Chan, Queenie
<x xml:space="preserve">Abstract</x> Purpose To prospectively evaluate the dynamic contrast‐enhanced magnetic resonance imaging (DCE‐MRI) value for predicting early nasopharyngeal carcinoma (NPC) chemoradiotherapy (CRT) response. Materials and Methods Forty‐two patients with advanced NPC were recruited and received three DCE‐MRI exams before treatment (Pre‐Tx), as well as 3 days (Day 3‐Tx) and 40 days (Day 40‐Tx) after chemotherapy initiation (two neoadjuvant chemotherapy cycles, NAC). We used DCE‐Tool to measure primary tumor kinetic parameters (Ktrans, Kep, ve, and vp) using the extended Tofts model. Kinetic parameters and corresponding changes were compared between responders and nonresponders after NAC or CRT treatment using Student's t or Mann–Whitney U tests. Results Response to two NAC cycles correlated with short‐term local control (P = 0.01). Compared to the nonresponder group, the responder group presented with significantly larger ΔKtrans(0–3), ΔKep(0–3), and Δvp(0–3) values after NAC (P < 0.05). The complete response group after CRT exhibited significantly lower Ktrans(Day 40‐Tx) and larger ΔKtrans(0–3) values than the residual group (P = 0.05). High sensitivity (range: 74.1%–90%) and moderate‐to‐high specificity (range: 50%–84.3%) distinguished nonresponders from responders grouping after NAC or CRT, with diagnostic efficiency ranging from 69.3%–88%. Conclusion Our study showed kinetic parameter changes earlier after chemotherapy were potential markers for NPC patients receiving CRT therapy following NAC. J. Magn. Reson. Imaging 2015;41:1528–1540. © 2014 Wiley Periodicals, Inc.